Specificity of blood clotting parameters in hemorrhagic stroke (Texas Journal of Medical Science, 2024)
The article describes the specificity of blood clotting parameters such as hematocrit number, thrombin time, fibrinogen, standard test, thrombotest in hemorrhagic stroke, and these values depend on various co-morbid conditions and age and sex of patients. Hemorrhagic stroke is becoming more prevalent and is one of the most pressing medical and social problems. Cardiovascular and endocrine diseases are in creasing the incidence of hemorrhagic stroke as a background, and the effects on the vascular walls as well as the rheological properties of the blood are known. As a result, patients have varying degrees of neurological disorders and premature death.